Distribution Of The Breast Lesions Based On The Mammogram Scoring Among Different Age Groups - Safiya Mohammed; Alaa Mirza Hussain (Kufa Journal for Nursing Sciences)
Background: The mammary glands are prone to various lesions, either benign or malignant, many of benign types that can mature to malignant if untreated. The breast glandular structure can undergo changes from puberty to pregnancy and menopause due to hormonal effects, so the type of lesion occurrence among women varies depending on the age.